Membranoproliferative glomerulonephritis: A rare pediatric nephropathy - Andreia Marinhas; Telma Luís; Catarina Neves; Carmen Carmo; Clara Gomes (Publicações Ciência e Vida, 2022)
Membranoproliferative glomerulonephritis is a rare chronic glomerulonephritis in pediatric age. It may be a primary disorder or secondary to other chronic diseases. Diagnose of membranoproliferative glomerulonephritis is based on specific kidney biopsy findings. The prognostic factors, the outcome and the most suitable treatment regimen are incompletely known in children. We report a case of a 3-year-old boy that presented with nephritic/nephrotic syndrome and hypocomplementemia. After 10 days under corticosteroid therapy, he maintained worsening of renal function and a renal biopsy specimen revealed a membranoproliferative glomerulonephritis. Autoimmune disease and infections were initially excluded, but further investigation revealed positive Polymerase Chain Reaction for cytomegalovirus in blood and urine. Cytomegalovirus genome at biopsy was not identified. He completed six months of treatment with valganciclovir and corticosteroids with total remission of proteinuria and undetected viral loads. With this case, we would like to draw attention to a type of nephropathy that is rare in childhood.